2019
DOI: 10.7717/peerj.7694
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biomimetic material on stress distribution in mandibular molars restored with inlays: a three-dimensional finite element analysis

Abstract: Background Although biomimetic material has become increasingly popular in dental cosmetology nowadays, it remains unclear how it would affect the restored teeth during chewing. It is necessary to study the influence of biomimetic material on stress distribution in the restored teeth. Methods Eight three-dimensional finite element (FE) models were constructed and divided into two groups. Group 1 included the FE model of intact molar, and the FE models of inlay-restored molars fabricated from IPS e.max CAD, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…A restoration must resist natural forces that occur in the mouth [14][15][16] . A 45-degree angle to the long axis of the tooth was chosen to match the lateral the force (eccentric force) applied on the teeth during mastication 12,[17][18][19][20] while an 11-degree angle to the long axis of the tooth was chosen to match the applied perpendicular force (centric force) on the teeth (90 degrees) during mastication 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A restoration must resist natural forces that occur in the mouth [14][15][16] . A 45-degree angle to the long axis of the tooth was chosen to match the lateral the force (eccentric force) applied on the teeth during mastication 12,[17][18][19][20] while an 11-degree angle to the long axis of the tooth was chosen to match the applied perpendicular force (centric force) on the teeth (90 degrees) during mastication 10 .…”
Section: Discussionmentioning
confidence: 99%
“…After the models were meshed, two different oblique forces each of 100N [14][15][16] were applied as two load cases, one at (11º) 10 and the other at (45º) 10,14-18 from the vertical long axis of the tooth. Each load was equally divided on 15 points representing; outer, inner surface cusp tips of labial cusp, inner surface of lingual cusp, central and mesial triangular fossa distal and mesial marginal ridge 18 as presented in (Figure 1). Thus, totally six runs were performed on the two models as following:-Two runs on the model1 (one at 11º and other at 45º) from vertical axis and four runs on CMR materials of model II (one run at 11º and other at 45º on Dyract Flow) & (one run at 11º and other at 45º on Riva light cure glass ionomer) from the vertical axis 10,13 .…”
Section: Application Of Load and Boundary Conditionsmentioning
confidence: 99%
“…Moreover, Tortopidis et al [50] measured a maximum biting force of 580 N in healthy people's posterior areas. Besides the tooth loading level, the restorative procedure has been identified as another parameter influencing the stress and strain levels of restored teeth [19,20,35,38,41,43,51]. All researchers reported that teeth with onlay restorations appear more resistant to fracture than those with inlay restorations.…”
Section: Discussionmentioning
confidence: 99%
“…Boundary conditions were applied in the five faces of the box that supported the teeth, assuming that the faces were connected to the remaining maxillary bone and, therefore, the three nodal displacements of all nodes placed over those faces were restrained. The load was applied on a 28.3 mm 2 circle as a homogenously distributed pressure corresponding to an oblique load of 500 N at 30 • to the tooth axis (Figure 2c) [37,38]. The loads were applied gradually to avoid dynamic effects and convergence problems.…”
Section: Numerical Modelsmentioning
confidence: 99%
“…Esses materiais tem a capacidade de mimetizar as características originais da estrutura dentária de forma mais eficiente, tais como: pinos de resina reforçados por fibra de vidro, resinas compostas e sistemas cerâmicos, incluindo as porcelanas 2,3 .…”
Section: Introductionunclassified